Effectiveness of Online Multicultural Education During The Covid-19 Pandemic - Dadang Emuh (Jurnal Mantik, 2021)
This study uses descriptive qualitative methods and a multi-site approach, data collection techniques by observation, in-depth interviews and documentation review. The data were analyzed interactively through three parts, data reduction, data presentation and conclusion drawing. Checking the validity of the data using triangulation techniques. The results of the study answered that the participation and role of teachers in other religious rituals did not participate and play a role in other religious rituals but always respected them in a friendly manner, the response of parents to the implementation of multicultural Islamic education was always supportive, very good, and responded very positively, the response of community members to the implementation of multicultural Islamic education was happy and enthusiastic, there were no negative views or conflicts from them. all students, teachers, parents, religious leaders and the community are all involved.